2014
DOI: 10.1515/ijnsns-2012-0064
|View full text |Cite
|
Sign up to set email alerts
|

On the Sandpile Model of Modified Wheels I

Abstract: In this paper, we investigate the sandpile group of modified wheelsŴ 2n by using a variant of the chip firing game [6] defined on this family of graphs. The family of modified wheelsŴ 2n is defined by taking the simple wheel graph W n with n rim vertices and then adding two extra vertices on each of the rim edges. It has 3n þ 1 number of vertices and size 4n.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Its most celebrated contribution is perhaps its role in developping discrete Riemann-Roch and Abel-Jacobi theory on graphs [5]. The structure of the sandpile group has also been explicitly computed on a variety of graph families, including complete graphs [18], nearly-complete graphs (complete graphs with a cycle removed) [41], wheel graphs [9] (see also [35,36]), Cayley graphs of the dihedral group D n [20], and many more (see e.g. [15] and the references therein for a more complete list).…”
Section: Introductionmentioning
confidence: 99%
“…Its most celebrated contribution is perhaps its role in developping discrete Riemann-Roch and Abel-Jacobi theory on graphs [5]. The structure of the sandpile group has also been explicitly computed on a variety of graph families, including complete graphs [18], nearly-complete graphs (complete graphs with a cycle removed) [41], wheel graphs [9] (see also [35,36]), Cayley graphs of the dihedral group D n [20], and many more (see e.g. [15] and the references therein for a more complete list).…”
Section: Introductionmentioning
confidence: 99%
“…In [1], it has been shown that the set of critical configurations can be used to give the structure of an abelian group by giving critical configurations for a wheel graph W n . For general references on the ASM (denoted by SP (G,q)), see, e.g., [5][6][7][8][9][10][11][12][13][14] and on the critical group (denoted by K(G)), see for instance [15][16][17][18][19][20][21][22][23][24]. The definitions and statements of theorems presented in this section have been taken from [1].…”
Section: Introductionmentioning
confidence: 99%
“…When we delete, from ∆Γ, the row and column corresponding to the sink, we obtain the reduced graph Laplacian ∆ Γ . The sandpile group G Γ is then defined as the cokernel of ∆ Γ acting on Z Γ [25,12,45,1], i.e. faces, as these morphisms directly induce epimorphisms between the respective sandpile groups [9] (see also [46,2]).…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Only for few infinite families of graphs, the structure of the respective sandpile groups has been (partly) determined, including complete graphs [39], complete multipartite graphs [29], cycles (equivalent to domains of Z 1 ) [39], thick cycles [1] (see also [26]), wheels [12,43], modified wheels [45], wired regular trees [38], thick trees [19], polygon flowers [17], nearly complete graphs [43], threshold graphs [43], Möbius ladders [18,24], prism graphs/graphs D n of the dihedral group [23,24], and n-cubes [6,2]. While this list is certainly not complete, the decomposition of the sandpile group on domains of Z 2 , for which the sandpile model was originally defined [7], is-to our knowledge-yet unknown.…”
Section: Introduction 1backgroundmentioning
confidence: 99%